Numbers over Narratives? How Government Message Strategies Affect Citizens' Attitudes. Issue 5 (3rd September 2019) - Piotrowski, Suzanne; Grimmelikhuijsen, Stephan; Deat, Felix
ABSTRACT: This article applies different marketing concepts to released government information and analyzes the effect on citizens' attitudes. It looks at how the presentation of a message affects citizens' attitudes when the content remains the same. It investigates the effects of an informational strategy (presenting facts and figures) and a transformational strategy (adding narratives to the figures to appeal to emotions of citizens). Based on theories about information process and framing, different responses are expected from engaged and unengaged citizens. It finds that unengaged citizens respond more favorably when information is couched in a transformational message strategy. Engaged citizens have an opposite response and are better served with an informational strategy. The article concludes that to reach the broader group of unengaged citizens, just disclosing information is insufficient; information needs to be embedded in a meaningful narrative.